Workplace learning :a study of learning approaches in two organisations in Sarawak - Bong, Er Huen (Universiti Malaysia Sarawak, UNIMAS, 2007)
The purpose of this study is to analyse t he types of learning a pproaches used in two organisations in Sarawak and the factors influencing it. A survey questionnaire was used to collect data for this study. Eighty respondents were selected from two organisations: P ublic W ork D epartment (PWD) Sarawak and Syarikat SESCO Berhad . The data gathered were analysed using both descriptive and inferential statistics. Descriptive statistics was used to describe respondents’ personal characteristics such as gender, age, educational level, length of service and monthly income. Infer ential statistics such as Pearson Correlation Coefficient was used to determine whether there exist s a significant relationship between the independent variables and learning approaches. The findings show that the majority of respondents (78.7%) frequently use informal learning approaches such as conducting discussions with colleagues and supervisors, and obtaining information through resource centres, the Internet, books, magazines and other reading materials in the workplace. In contrast, only a minority of the respondents (11.2%) very often use formal learning approaches in the workplace. Analysis of the results also found that there exist significant positive relationship s between the two independent variables – learning att itude and environmental suppor t – and learning approaches used in the workplace. Howev er, both relationships are weak : between learning attitude and learning approaches ( r = 0.540) , and between environmental support and learning approaches ( r = 0.443). Several recommendations are sugge sted to the organisations, human resource practitioners and for future research in order to encourage continuous learning in the workplace and to help enhance employees’ work performance.